Motives for writing - Miller, Robert Keith (Boston, MA : McGraw-Hill, 2006)
From the Publisher: This collection of primarily contemporary readings is organized around the various rhetorical purposes that motivate writers. Including detailed guides to writing motives such as Analyzing Texts, Analyzing Images, and Writing Arguments, this text provides a rhetorically grounded approach to academic writing and research
Keywords: College readers; Report writing; English language